2012
DOI: 10.1002/lemi.201290115
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR screening of pharmacologically active substances in weight‐loss supplements being sold online

Abstract: Weight-loss or slimming food supplements may be adulterated with synthetic pharmaceuticals, such as anorectic, anxiolytic and antidepressant compounds, especially when sold over the internet. An NMR screening method to detect these pharmacologically active compounds in slimming products is introduced in this study. As a first step, we gathered NMR-related information ( chemical shifts, multiplicity ) both from the scientific literature and own theoretical spectra prediction for 53 substances, which are likely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…1 H NMR is useful for qualitative and quantitative analysis of constituents in medicinal plants and herbal products 24 . However, NMR has, so far, not received a wider application in the official food supplements testing and medicine control laboratories than other chromatographic methods, mostly because the NMR technique was judged to be complicated and instruments too expensive 25 . However, several improvements in instrumentation during the last decade have made NMR available for routine applications 25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 H NMR is useful for qualitative and quantitative analysis of constituents in medicinal plants and herbal products 24 . However, NMR has, so far, not received a wider application in the official food supplements testing and medicine control laboratories than other chromatographic methods, mostly because the NMR technique was judged to be complicated and instruments too expensive 25 . However, several improvements in instrumentation during the last decade have made NMR available for routine applications 25 .…”
Section: Discussionmentioning
confidence: 99%
“…However, NMR has, so far, not received a wider application in the official food supplements testing and medicine control laboratories than other chromatographic methods, mostly because the NMR technique was judged to be complicated and instruments too expensive 25 . However, several improvements in instrumentation during the last decade have made NMR available for routine applications 25 . In the future, a metabolomic approach using NMR would be useful for large-scale analysis of Garcinia food supplements and this study has shown that qNMR is a fast and sensitive enough method for the quantification of (−)-hydroxycitric acid content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 9: Mass fragmentation pattern and fragment compounds of the compound Sibutramine and its analogues. (Roh et al, 2011) Methods involving LC coupled with various detectors (usually MS), have the advantage of high sensitivity; however, they also have disadvantages of being laborious, time consuming and the fact that they are too selective and cannot provide global information in detecting a particular component, because compositions of drugs vary among different brands (Monakhova et al, 2012). These methods were also considered to have inadequate reliability for screening because herbal medicines contain a complex mixture of many components which may interfere with chromatographic and mass spectroscopic assays (Calahan et al, 2016).…”
Section: Quadrupole Time Of Flight Liquid Chromatography Mass Spectromentioning
confidence: 99%
“…NMR spectroscopy allows the simultaneous detection and quantification of compounds belonging to different chemical classes: sugars, organic and amino acids, flavonoids, alkaloids, terpenoids, and others. This method was applied to the classification and characterization of different medicinal plants, as well as to the detection of the adulteration of plant materials [ 16 , 17 , 18 , 19 ]. The objective of this study is to assess the differences in proximate and metabolic compositions of H. sabdariffa calyces using NMR metabolomics from plants collected in different locations in India and dried using the shade drying (SD) and tray drying (TD) techniques.…”
Section: Introductionmentioning
confidence: 99%